Taxonomic review of the Oriental flower beetle Coilodera penicillata species complex (Coleoptera: Scarabaeidae: Cetoniinae) - Qiu, Jian-Yue; Xu, Hao; Chen, Li (Zootaxa, 2017)
The taxonomy of the Coilodera penicillata Hope, 1831 (Coleoptera: Scarabaeidae: Cetoniinae) species complex, which is recognized by the black body and elytra with larger tomentose maculae, is revised. Six Indochinese species assigned to this complex, including C. grandimaculata new species from Tibet, China. Coilodera nigroscutellaris Moser, 1902 revised status and C. formosana Moser, 1910 revised status formerly treated as two subspecies of C. penicillata Hope, 1831 are elevated to species rank. The distribution of C. penicillata in China is confirmed based on examination of specimens from Yunnan and Tibet, and almost all previous Chinese literature records should be referred to C. nigroscutellaris. Coilodera dives (Gory & Percheron, 1833) revised status previously synonymized with C. penicillata is herein considered as a valid species based on the examination of types and additional specimens, and C. miksici Antoine, 1986 new synonymy is regarded as a junior synonym of C. dives. A lectotype is designated for Coilodera dives (Gory & Percheron, 1833). The record of C. mearesii (Westwood, 1842) in southeastern China is attributed to a misidentification of C. nigroscutellaris, and it is here newly recoreded from Tibet near the Nepal-China border. Diagnosis characters and intraspecific variations are illustrated for all six species, new distribution records and a key to species are also presented. Ecological information is provided for all species.